Evidence for activation of nitenpyram by a mitochondrial cytochrome P450 in Drosophila melanogaster. Issue 7 (26th February 2018) - Harrop, Thomas WR; Denecke, Shane; Yang, Ying Ting; Chan, Janice; Daborn, Phillip J; Perry, Trent; Batterham, Philip
Abstract: BACKGROUND: Nitenpyram is a member of the economically important neonicotinoid class of insecticides. The in vivo metabolism of nitenpyram is not well characterised, but cytochrome P450 activity is the major mechanism of resistance to neonicotinoids identified in insect pests, and P450s metabolise other neonicotinoids including imidacloprid. RESULTS: Here, we used the GAL4‐UAS targeted expression system to direct RNA interference (RNAi) against the cytochrome P450 redox partners to interrupt P450 functions in specific tissues in Drosophila melanogaster . RNAi of the mitochondrial redox partner defective in the avoidance of repellents ( dare ) in the digestive tissues reduced nitenpyram mortality, suggesting an activation step in the metabolism of nitenpyram carried out by a mitochondrial P450. RNAi of the mitochondrial cytochrome P450 Cyp12a5, which is expressed in the digestive tissues, resulted in the same phenotype, and transgenic overexpression of Cyp12a5 increased nitenpyram sensitivity. CONCLUSION: These results suggest that in vivo metabolism of nitenpyram by the mitochondrial P450 CYP12A5 results in the formation of a product with higher toxicity than the parent compound. © 2018 Society of Chemical Industry Abstract : The in vivo metabolism of nitenpyram is not well characterised, but cytochrome P450 activity is the major mechanism of resistance to neonicotinoids identified in insect pests, and P450s metabolise other neonicotinoids including imidacloprid.